Sandstone composition of the Valdez and Orca Groups, Prince William Sound, Alaska - Dumoulin, Julie A.; Geological Survey (U.S.) (Washington : United States Government Printing Office, 1987)
Shipping list no.: 1987-667-P. Includes bibliographical references (pages 34-37). Mode of access: Internet.